Analisis Faktor-Faktor yang Memengaruhi Produktivitas Tenaga Kerjapada Proyek Konstruksi Bangunan Gedung Baru RSU Bunda Padang - Rendi Fatria Yusra; Rini Mulyani; Yulcherlina (Jurnal Teknik Sipil Institut Teknologi Padang, 2026)
The implementation of construction projects is required to achieve optimal quality, be completed on time, and within the planned budget. In the effort to achieve that success, labor productivity becomes one of the important factors that greatly influence the smooth execution of the project. A low level of labor productivity can cause various negative impacts, such as delays in project completion, increased implementation costs, and a decline in the quality of the work results. Therefore, an analysis of the factors affecting labor productivity is necessary so that the project implementation can run more effectively and efficiently. This study aims to identify the factor with the highest relative importance that affects labor productivity in the construction project of the RSU Bunda Padang building. The research method used is a quantitative method with data collection thru the distribution of questionnaires to respondents involved in the project. The data obtained were then analyzed using IBM SPSS V20 software to conduct validity and reliability tests. Next, the Relative Importance Index (RII) analysis is used to rank the factors that most influence labor productivity in the construction project. Based on the results of the validity and reliability tests, out of the 20 research variables, 19 variables were declared valid and reliable. The RII analysis results show that the availability of materials is the most influential factor on labor productivity, with an RII value of 0.9608.